PENERAPAN MODEL INQUIRI TERBIMBING BERBASIS SCAFFOLDING METAKOGNITIF UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS BERDASARKAN TAHAPAN PERKEMBANGAN KOGNITIF SISWA SMA - Anissa Listiana Maharani; Hepsi Nindiasari; Abdul Fatah (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2020)
The ability of mathematical reflective thinking (KBRM) is the ability of a person to review, monitor, and process their own solutions in solving mathematical problems. To practice thinking skills, the teacher must train students according to the scheme at the stages of cognitive development so that a meaningful learning is created. Learning with a guided inquiry model based on scaffolding metacognitive (ITBSM) has a great chance of being able to improve mathematical reflective thinking skills (KBRM) of high school students. This research was conducted at SMAN 1 Baros, Serang Regency, Banten Province with a sample of class X MIPA. This study revealed an increase in the KBRM of students with the treatment of guided inquiry models based on scaffolding metacognitive (ITBSM) was better than expository learning with a sig value. 0.050 for the whole and sig. 0,000 for concrete cognitive levels. Tests were carried out descriptively and inferentially by processing data using shapiro-wilk, lavene test, parametric two-way anova test and one-way ANOVA test, Mann Whitney U non parametric test and Wallis H. Kruskall test. Keywords : Mathematical Reflective Thinking Ability, Guided Inquiry, Scaffolding, Metacognitive